Aliyev, Alasgar - (:unkn) unknown (My University, 2026)
Alasgar Mehdi Aliyev was born on May 9, 1954, in the Turkmen village of Barda, Azerbaijan. He completed his primary education in his native village and graduated with a gold medal from Secondary School No. 4 in Barda in 1970. In the same year, he entered the Faculty of Construction at the Azerbaijan Polytechnic Institute, where he earned a degree in Economics and Organization of Construction with the qualification of Engineer-Economist. Following his military service, he began his professional career at the Economics Institute under the State Planning Committee of the Republic of Azerbaijan, where he worked as an economist and junior researcher. In 1979, he was admitted to the full-time postgraduate program at the Azerbaijan Institute of National Economy. After successfully completing his postgraduate studies in 1982, he was appointed by the Ministry of Education to the Azerbaijan Institute of Civil Engineers (now the Azerbaijan University of Architecture and Construction). Since then, he has served as a senior laboratory assistant, assistant lecturer, senior lecturer, and, since 1994, Associate Professor. In 1984, he defended his Candidate of Sciences (PhD equivalent) dissertation in the specialty 08.00.05 – Economics and Management of the National Economy at the Azerbaijan Institute of National Economy. His dissertation was entitled Improvement of Planning of Fixed Assets and Increasing Economic Efficiency. Associate Professor Alasgar Mehdi Aliyev is the author of more than 150 scientific publications published both in Azerbaijan and internationally, including two textbooks, two monographs, and 45 educational curricula. He has served as a member of numerous specialized dissertation councils and has acted as an official opponent for dozens of doctoral and candidate dissertations.